What If They Were White? The Differential Arrest Consequences of Victim Characteristics for Black and White Co-offenders. (8th September 2021) - Lantz, Brendan; Wenger, Marin R; Craig, Chloe J
Abstract: A substantial body of research focuses on racial disparity in the criminal justice system, with mixed results due to difficulty in disentangling differential offending from racial bias. Additionally, some research has demonstrated that victim characteristics can exacerbate racial disparity in outcomes for offenders, but little research has focused on the arrest stage. We use a quasi-experimental approach that examines incidents involving co-offending pairs to isolate the influence of offender race on arrest, beyond any characteristics of the incident itself, and we test for moderating effects of victim race and sex on racial disparities in arrest. Our findings reveal that, on average, when two offenders of different races commit the same offense together against the same victim, Black offenders are significantly more likely to be arrested than their White co-offending partners, especially for assault offenses. More importantly, this effect—for both assaults and homicides—is particularly strong when the victim is a White woman. Because these differences are between two offenders who commit the same offense together, we argue that the most plausible explanation for the differences is the presence of racial bias or discrimination.